2015
DOI: 10.1016/j.expneurol.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in monocarboxylate transporter 1 (MCT1) in mice delays regeneration of peripheral nerves following sciatic nerve crush

Abstract: Peripheral nerve regeneration following injury occurs spontaneously, but many of the processes require metabolic energy. The mechanism of energy supply to axons has not previously been determined. In the central nervous system, monocarboxylate transporter 1 (MCT1), expressed in oligodendroglia, is critical for supplying lactate or other energy metabolites to axons. In the current study, MCT1 is shown to localize within the peripheral nervous system to perineurial cells, dorsal root ganglion neurons, and Schwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 47 publications
4
75
0
Order By: Relevance
“…We did not observe any change in lactate levels in the SN, but this does not preclude alterations in the flux of lactate between neurons and glia. Lactate transfer is mediated by the monocarboxylate transporters (MCTs), of which MCT-1 is the main isoform expressed in peripheral nerves (29). We identified/quantified MCT-1 in both the SN and the DRG but did not observe significantly altered expression in either tissue (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…We did not observe any change in lactate levels in the SN, but this does not preclude alterations in the flux of lactate between neurons and glia. Lactate transfer is mediated by the monocarboxylate transporters (MCTs), of which MCT-1 is the main isoform expressed in peripheral nerves (29). We identified/quantified MCT-1 in both the SN and the DRG but did not observe significantly altered expression in either tissue (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…Unlike the CNS, however, there are no published studies demonstrating the critical nature of lactate to peripheral nerve function in vivo under normal physiologic conditions. As discussed in greater detail below, we have shown that lactate transporters are important for the response of peripheral nerves to injury (Morrison et al, 2015). …”
Section: Fuels To Neural Cells: Glucose Its “By-product” Lactate Anmentioning
confidence: 99%
“…In addition to therapeutically addressing the plethora of inflammatory mediators present, remyelination of axons is considered as one of the most important endogenous axon‐protective mechanisms. Aside from restoring the conductive properties of the axon, remyelination provides insulation of the axon against a potentially hostile microenvironment and restores the close metabolic interaction with oligodendrocytes (Fünfschilling et al, 2012; Lee et al, 2012; Morrison et al, 2015). The correlation of early remyelination and axonal damage and whether damaged axons can be remyelinated, is unknown so far.…”
Section: Introductionmentioning
confidence: 99%